2016
DOI: 10.3892/or.2016.4580
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of mitogen-activated protein kinase signaling pathway sensitizes breast cancer cells to endoplasmic reticulum stress-induced apoptosis

Abstract: Abstract. Accumulation of unfolded proteins in the endoplasmic reticulum (ER) induces ER stress which is observed in many human diseases, including breast cancer. Cellular adaptation to ER stress is mediated by the unfolded protein response (UPR), which aims at restoring ER homeostasis. Higher levels of GRP78 expression indicates constitutive activation of the UPR in breast cancer leading to breast cancer cells that are relatively resistant to ER stress-induced apoptosis. Tunicamycin (TM), an ER stress inducer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…To quantify Ki67 expression, both the intensity and extent of immunoreactivity were evaluated and scored. IHC staining and score evaluation were performed according to standard protocols as described previously [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…To quantify Ki67 expression, both the intensity and extent of immunoreactivity were evaluated and scored. IHC staining and score evaluation were performed according to standard protocols as described previously [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…19 Targeting at the PI3K/ AKT/mTOR signaling pathway, a dual PI3K/mTOR inhibitor, BEZ235, was developed to inhibit tumor growth, 20 the mechanism of which might be partially attributed to phosphorylation of relevant proteins in the PI3K/AKT/mTOR signaling pathway. 19 Yang et al 21 have reported that PI3K/AKT signaling pathway, one of the survival signaling pathways, plays an important role in resisting the apoptosis-inducing ability of ERS. Moreover, it has been proved that BEZ235 inhibited MCF-7 cell proliferation via the PI3K/AKT/mTOR signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…A recent publication using pathway network analyses revealed a major overlaps with various diseases and convergence upon MAPK and calcium signaling as well [11]. Studies using U0126, a selective MAPK kinase (MKK) inhibitor [12], have revealed a major effect on the deactivation of ERK1/2 [13] possibly even affecting MAPK-mediated mitochondrial-derived [14] and endoplasmic reticulum stress induced apoptosis [15]. …”
Section: Introductionmentioning
confidence: 99%